The Effect of Kaempferol on Cortical Nlrp3/Caspase-1/Gsdmd Mediated Cell Pyroptosis in Chronic Epileptic Rats - Yang, Guang; Cai, Rui (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim To study the Kaempferol (Kaem) on Pentetrazol (PTZ)-induced chronic epileptic rats, and to explore its effect on nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3)/ caspase-1/gasdermin D (GSDMD)-mediated pyroptosis in the cerebral cortex and its possible mechanism. Materials and Methods Six rats were randomly selected from 30 SPF male SD rats as the normal group, and the remaining rats were intraperitoneally injected with PTZ (35 mg/kg) for 28 d to replicate the chronic epilepsy model. The 18 successfully modeled rats were randomly divided into model, low-dose Keam (Kaem-L), Middle-dose Keam (Keam-M) and high-dose Kaem (Kaem-H) groups, with 6 rats in each group. The rats in Kaem-L, Keam-M and Kaem-H groups received 1, 2 and 10 mg/kg of Kaem by continuous lavage for 14 d, while those in normal and model groups were given equal volume of saline. The latency of Generalized Tonic-Clonic Seizures (GTCS) and Minimal Clonic Seizures (MCS) was recorded. The pathological changes of the temporal lobe cortex were observed by HE staining. Neuronal apoptosis was detected by TUNEL staining. The protein levels of NLRP3, caspase-1 and GSDMD in the cortex were detected by immunohistochemical staining and Western blot. The expression levels of TNF-α, interleukin-18 (IL-18) and IL-1β in brain tissue were detected by immunohistochemical staining. The mRNA expression levels of NLRP3, caspase-1 and GSDMD in the cerebral cortex were detected by RT-qPCR. Results Compared with normal group, the latency of GTCS and MCS in the rats of model group was significantly shortened (p<0.01). Compared with normal group, the number of apoptotic cortical neurons in model group was significantly increased. The protein expression levels of TNF-α, IL-18 and IL-1β in the cortical tissues were significantly increased, and the mRNA and protein expression levels of NLRP3, caspase-1 and GSDMD were also significantly increased (P<0.01). Compared with model group, the latency of GTCS and MCS in Kaem treated groups was significantly prolonged, the number of apoptotic cortical neurons in rats was significantly reduced, the protein expression levels of TNF-α, IL-18 and IL-1β in cortical tissue was reduced to varying degrees, and the mRNA and protein expression of NLRP3, caspase-1 and GSDMD also showed varying degrees of reduction (p<0.01). Conclusion The Kaem may reduce the secretion of inflammatory factors and inhibit the pyroptosis of nerve cells through the NLRP3/caspase-1/ GSDMD signaling pathway, thus playing a therapeutic role in chronic epileptic rats induced by PTZ.
Keywords: Epilepsy; Kaem; NLRP3/caspase-1/GSDMD signaling pathway; Pyroptosis.